First Synthesis and Characterization of CH4@C60. Issue 15 (12th March 2019) - Bloodworth, Sally; Sitinova, Gabriela; Alom, Shamim; Vidal, Sara; Bacanu, George R.; Elliott, Stuart J.; Light, Mark E.; Herniman, Julie M.; Langley, G. John; Levitt, Malcolm H.; Whitby, Richard J.
Abstract: The endohedral fullerene CH4 @C60, in which each C60 fullerene cage encapsulates a single methane molecule, has been synthesized for the first time. Methane is the first organic molecule, as well as the largest, to have been encapsulated in C60 to date. The key orifice contraction step, a photochemical desulfinylation of an open fullerene, was completed, even though it is inhibited by the endohedral molecule. The crystal structure of the nickel(II) octaethylporphyrin/ benzene solvate shows no significant distortion of the carbon cage, relative to the C60 analogue, and shows the methane hydrogens as a shell of electron density around the central carbon, indicative of the quantum nature of the methane. The 1 H spin‐lattice relaxation times ( T 1 ) for endohedral methane are similar to those observed in the gas phase, indicating that methane is freely rotating inside the C60 cage. The synthesis of CH4 @C60 opens a route to endofullerenes incorporating large guest molecules and atoms. Abstract : The endohedral fullerene CH4 @C60 has been synthesized for the first time using photochemical desulfinylation of an open fullerene as the key step. Methane is a much larger molecule than has been previously encapsulated in the closed C60 cage and is amongst the largest of possible guests.